Ali lahko napovemo izostanek oploditve jajčnih celic v postopkih zunajtelesne oploditve? - Rakić, Ksenija (Zdravniški vestnik, 2011)
Objective: To analyze predictors of the IVF cycles with high risk of total fertilization failure (TFF). Methods: A retrospective analysis of 981 consecutive stimulated IVF cycles with successful oocyte retrieval. IVF cycles were divided into two groups. Group 1 consisted of IVF cycles with fertilization and group 2 of IVF cycles in which none of the oocytes were fertilized (TFF). The groups were compared according to female age, indications for IVF, stimulation protocol, number of oocytes and semen quality. Nonparametric statistics was used. Logistic regression and receiver operating characteristic (ROC) curve were used to determine which variables could be used to predict TFF. Result(s): TFF appeared in 84 (8.6 %) cycles. There were statistically significant differences in female age, number of oocytes, total and motile sperm concentration between the groups. Univariate logistic regression analysis showed significant prediction of TFF by duration of stimulation, number of ampoules used, number of oocytes and motile sperm concentration. According to multivariate analysis, the only two variables that can predict TFF are the number of oocytes (OR 1.25, p = 0.000) and motile sperm concentration (OR 1.01, p = 0.03). With ROC analysis we have determined that the number of oocytes and motile sperm concentration have good predictive value for TFF. The most appropriate cut-off value for number of oocytes was 3, with 81.1 % sensitivity and 60.0 % specificity. We did not manage to define appropriate cut-off value, which could predict TFF for motile sperm concentration. The area under the curve (AUC) for number of oocytes was 0.754, p = 0.000 and for motile sperm concentration 0.631, p = 0.000. Conclusion(s): According to our results, TFF in IVF cycles can be predicted only by low number of oocytes (poor responders) and lower motile sperm concentration.
Keywords: fertilization; jajčne celice; oploditev; spermiji; zunajtelesna oploditev